An Honest Day's Pay: Cooperation among Entrepreneurs vs. Students, and Linkages to Real‐World Business Success. (31st July 2019) - Batsaikhan, Mongoljin; Putterman, Louis
Abstract : The importance of cooperative behavior in business environments has been theorized in the field of management. However, measuring cooperation quantitatively is often challenging. We take advantage of experimental methods to overcome this issue. Particularly, we study the decisions that small‐scale entrepreneurs in Ulaanbaatar, Mongolia, make in a laboratory property rights dilemma experiment, comparing these to the decisions of student counterparts in the same and other countries, and looking for correlations between lab decisions and success in real‐world business sales. We find that Mongolian entrepreneurs generally achieve much higher cooperation levels and hence higher experimental earnings than Mongolian students. Also, among individual participants, producing and desisting from theft in the lab setting is correlated at the 1% level with real‐world business sales. Our findings align with the view that cooperative impulses or abidance of social norms can be an advantage in business relationships.